Ruptured aneurysm of right sinus of valsalva - a case report (Bangladesh Medical Journal, 2016)
The sinus of valsalva aneurysm (SVA) is a small dilatation caused by a separation between the aortic media and annulus fibrosus. It may be either acquired or congenital. The right coronary sinus is most frequently affected, with the most common complication being rupture of the sinus. Cardiac failure and sudden auscultation changes suggest the possibility of SVA rupture. Echocardiography is sufficient to diagnose SVA, its complications, repercussions and to determine surgical options. SVA, even if asymptomatic, has potential risks of expansion, rupture, cardiac failure, endocarditis, embolism and sudden death. This justifies surgical correction which has a low mortality rate in both the short and long-term.Bangladesh Med J. 2015 Sep; 44 (3): 175-177